PENGARUH KOMPOSISI BAHAN DASAR BOKHASI PLUS DAN INTENSITAS NAUNGAN TERHADAP PERTUMBUHAN AWAL TANAMAN JAHE (Zingiber officinale Roxb. var.Rubra) - Nurlianti Nurlianti; Prihahani Prihanani (University of Prof. Dr. Hazairin, SH, 2015)
This study aims to getting the raw material composition Bokhasi Plus and the intensity of sunlight is sufficient under the palm trees on the early growth of ginger. Research has been conducted in the village of Suka Raja Seluma Bengkulu. Implementation research starting in July 2015 to November 2015. The results showed that treatment with the composition nutris higher raw material bokhasi (K1) with a combination of ginger plant under the palm stands with low light intensity (N3) shows the best growth in all variables observed.Keywords: The composition of the base material bokhasi, shade